The effects of swimming fatigue on shoulder strength, range of motion, joint control, and performance in swimmers. (January 2017) - Matthews, Martyn J.; Green, Daniel; Matthews, Helen; Swanwick, Emma
Abstract: Purpose: To investigate the effects of training induced fatigue on shoulder strength, ROM, joint position sense, and stroke length in elite competitive swimmers. Methods: Seventeen national level swimmers performed maximum isometric strength (internal and external rotation), ROM, and joint position sense tests before and after a fatiguing 8 × 100 m training set. Stroke length, heart rate, blood lactate and blood glucose levels were recorded throughout. Results: Peak blood lactate, blood glucose levels, and heart rate increased significantly (P < 0.001) post-training confirming fatigue. Reductions were observed in stroke length of both arms (P < 0.001), external rotation range of motion (P < 0.001,  −5.29°, Right shoulder; P = 0.04,  −3.18°, Left shoulder) and joint position sense in their dominant (breathing side) arm (P = 0.03). Conclusions: This investigation revealed a reduction in stroke length across both arms and also an arm bias in swimming whereby a greater reduction in both external rotation range and joint position sense was observed in the dominant arm when fatigued. This has highlighted a relationship between fatigue and potential mechanism of shoulder pathology in swimmers. Highlights: Reductions observed in swim stroke length with fatigue. Reductions observed in external rotation range of motion of both arms with fatigue. Reduction observed in joint position sense of dominant arm. No changes observed in isometric strength with fatigue.